Effect of head and PV array configurations on solar water pumping system. (2021) - Tiwari, Arunendra K.; Kalamkar, Vilas R.; Pande, Rohan R.; Sharma, Sanjay K.; Sontake, Vimal Chand; Jha, Abhishek
Abstract: Nowadays, the photovoltaic (PV) to power the water pumps is a newly accepted technology with few challenges associated with high initial cost and lower system efficiency. The literature suggests the majorly of commercial pumps at present, underperform, due to poor system design, low efficiency and mismatch of components. In this paper Matlab Simulink model of a solar photovoltaic (PV) water pumping system (SPVWPS) has been created. Such a model; demonstrates the system characteristics under different operating parameters. This model can successfully and completely check the feasibility, size and optimize the system for its complete utilization. The effect of various parameters such as operating head of the pump, radiation, PV array configurations on the performance of the SPVWPS has been discussed and presented in the paper.